Analisis Kritis Pemberitaan Pemaksaan Pengunaan Jilbab bagi Siswi Non Muslim SMKN 2 Padang di Metro TV - Martiniana Pasrin; Fathul Qorib; Latif Fianto (Universitas Merdeka Malang, 2022)
The news about the “forced” hijab for non-Muslim students at SMKN 2 Padang was crowded and became a national conversation. The mass media examines it from various sides with different emphases and approaches, one of which is the national media Metro TV. This study aims to see the construction and discourse built by Metro TV news that raised the case using the Critical Discourse Analysis, Teun van Dijk. The method used is descriptive qualitative with a critical paradigm. The study results show that Metro TV news considers the case part of intolerance, so the existing rules must be revised. The power used by Metro TV through the media channels is used to present two sources with different views. However, questions and conveying Metro TV's opinions led to the agreement that this case was part of the error in the regulations of the local government and the school.Keywords: Critical discourse analysis, Teun A. Van Dijk, corruption news discourse